(untitled) (Journal of Economic Research & Business Administration, 2016)
Ways of strategy of innovative development are considered in the article and is revealed, that a unique way of development for any country, including of Kazakhstan, is innovative way, which promotes increase competitiveness economy. Characteristics of an innovation, their levels and the problems of interfering their introduction are considered in the research. Development of processing industry is a priority task of all innovative strategy of the state. The paper examines the characteristics of innovation, their levels and challenges to their implementation. The article presents the principles of industrial – innovative government policies which aimed at the foundations, the strategic development plan, aimed at industrial – service technological economic of Kazakhstan. Also in this article have been identified directions of the post – industrial development ways in the perspective areas of science and technology innovation for increasing of the productive capacity for helping of the future competitive advantages in key areas of industrial – innovative policy of Kazakhstan.